Novel mutations in DNA2 associated with myopathy and mtDNA instability - Ronchi, Dario (Ann Clin Transl Neurol, 2019)
The maintenance of mitochondrial DNA (mtDNA) relies on proteins encoded by nuclear genes. Mutations in their coding sequences result in heterogenous clinical presentations featuring mtDNA instability in affected tissues. DNA2 is a multi‐catalytic protein involved in the removal of single strand DNA during mtDNA replication or Long Patch Base Excision Repair pathway. We have previously described DNA2 mutations in adult patients affected with familial and sporadic forms of mitochondrial myopathy. Here we describe four novel probands presenting with limb weakness associated with novel DNA2 molecular defects. Biochemical assays were established to investigate the functional effects of these variants.